2021
DOI: 10.21203/rs.3.rs-148266/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of Gel to the Transducer of Cartilage Conduction Hearing Aids Improves Their Benefits

Abstract: Gel is a conduction medium used to improve signal transmission and is applied in ultrasonography to obtain high-quality images; however, it is rarely used in hearing devices. The application of gel to couple the transducer to the ear could potentially improve the benefits of hearing aids, particularly cartilage conduction (CC) hearing aids, which deliver signals by vibration. The aim of this study was to investigate the impact of gel application on the efficacy of CC hearing aids in 23 patients (30 ears). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…A summary of the characteristics in the 12 included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] is shown in Table 2 . There was a total of 447 patients with various peripheral auditory disorders (excluding those from study [ 24 ] due to overlapping participant groups with study [ 20 ]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of the characteristics in the 12 included studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] is shown in Table 2 . There was a total of 447 patients with various peripheral auditory disorders (excluding those from study [ 24 ] due to overlapping participant groups with study [ 20 ]).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, 12 eligible papers were included in the review (Figure 2). A summary of the characteristics in the 12 included studies [14][15][16][17][18][19][20][21][22][23][24][25] is shown in Table 2. There was a total of 447 patients with various peripheral auditory disorders (excluding those from study [24] due to overlapping participant groups with study [20]).…”
Section: A Summary Of the Characteristics Of The Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation